Perspektif Kinerja Keuangan Bank Syariah di Indonesia - Aisjah, Siti; Kusumawati, Endah (Jurnal Aplikasi Manajemen, 2011)
Purpose - This study examines the implementation of financial performance system sharia bank based on Bank Indonesia regulatory No.9/1/PBI/2007 is CAMELS method. Design methodology/approach - The type of descriptive research and the sampling technique with the purposive sampling. Sharia Banks in Indonesia are a sample of Bank Sharia Mandiri, Bank Sharia Mega Indonesia and Bank Muamalat Indonesia. The data in the form of annual report, the calculation of profit and loss statements of retained earnings, as well as the Capial Adequecy Ratio. Year study period from 2007-2009. Methods of data analysis is the analysis of CAMEL. Findings-The results show that the financial performance of the national private sharia banks are better than the government of sharia banks. From the aspect of capital, management, and earnings, are both considered very good and very healthy otherwise. As for the aspect of asset quality and liquidity, the national private sharia banks tend to perform better than the government's sharia banks. Limitations/implications Limitations of this research method used is the CAMELS without examining the sensitivity factor (S).